Phases of Urban Development Impact on the Assessment of Thermal Comfort: A Comparative Environmental Study - Hala Hussein Musa; Aseel Mezher Hussein; Ammar N. Hanoon; Mahir M. Hason; Ali A. Abdulhameed (Salehan Institute of Higher Education, 2022)
Millions of pilgrims and visitors from numerous parts of the world flock to Karbala (one of the most prominent ideological and religious places in central Iraq) each year to visit the holy shrines in Karbala due to their sanctity. Many improvements have been made to the Two Holy Shrines (THS), the Shrines of Imam Husayn and Imam Abbas, and the area between them (ATHS), due to the high temperatures in this region and to improve pedestrian thermal comfort. Studies on improving outdoor thermal comfort in Karbala are scarce. Hence, this research aims to look into historical and current architectural changes and how they affect thermal comfort. On the hottest summer day, the ENVI-met software program was used to simulate the building design and calculate the impact of vegetation on outdoor thermal comfort. According to the findings, trees of medium-density in a compacted arrangement should be used nearby built-up structures in newly planned urban regions. In existing urban plots, the best approach is to use free blank areas (e.g. car parks) to set trees of medium-density, as well as plant along large pedestrian and driving routes. Doi: 10.28991/CEJ-2022-08-05-08 Full Text: PDF